Does Financial Attitude, Behavior, Knowledge, and Inclusion a Driving Factor in the Financial Capability of A Business Actor? - Rosalina, Silvia; Pratama, Bima Cinintya; Fakhruddin, Iwan; Wibowo, Hardiyanto (Politeknik Caltex Riau, 2023)
This research examines the influence of Financial Attitude, Knowledge, Behavior, and Inclusion on Financial Capability. The population used in this research was 19,044 business sectors in Banyumas, Brebes, and Cilacap Regencies. The sample calculation method in this research uses the Solvin technique so that the number of samples used in this research is 200 business sectors in Banyumas, Brebes, and Cilacap Regencies. The sampling technique used was the judgment sampling technique for MSMEs in Banyumas, Brebes, and Cilacap Regencies. This research uses the SEM (Structural Equation Modeling) analysis method with the Partial Least Square (PLS) approach which includes two models, namely the outer model and the inner model. The results of this research show that financial attitude, financial behavior, financial knowledge, and financial inclusion positively affect financial capability. Keywords: Financial Attitude, Financial Knowledge, Financial Behavior, Financial Inclusion, and Financial Capability.